DIGITAL TECHNOLOGIES AS NEW SUPPORTS FOR THE ECONOMY (Euro-Asia Conferences, 2021)
This article focuses on the rapidly evolving digital industry and the cryptocurrency market, which are currently experiencing a number of ups and downs. It provides information on issues related to cryptography and cryptanalysis, which are the basis of the digital currency market, the mechanism of transition from cryptography to cryptocurrencies, hashing functions, which are an important element of cryptography